Korelasi Nilai CBR Lapangan Dan CBR Laboratorium Untuk Lapisan Subgrade Pada Jalan Padang Tambak Liwa – Batas Kota Liwa - Yusuf, Roy Pramana; Jafri, Muhammad; Hadi, Yohanes Martono (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2018)
Land is the basis of a pavement structure. Best part of the land to construct a road construction is land that has a high density value. To determine the density of a soil, CBR testing is needed. CBR testing itself is divided into 2, namely field CBR and laboratory CBR. Location taken was between Padang Tambak Liwa - Liwa City Limits. This research will be conducted to find out how much influence the correlation of Field CBR values and Laboratory CBR on the road. In this study researchers will conduct Water Content Test, Filter Analysis, Atterberg Limits, Plastic Limit Test, Specific Gravity, Standard Soil Compaction, laboratory CBR Test, which uses disturbed subgrade from Padang Tambak Liwa - Liwa City Limits and then obtained a graph of the CBR laboratory test data results then compared with the existing field CBR graph. In the correlation of the value of the CBR field test and the laboratory CBR test there are samples that have an average deviation value below 5%. As for STA 227 + 500, STA 230 + 500, STA 233 + 000 there were different results of deviations from 26 samples, there were 3 samples that were above 5% deviation. This can be caused by uneven soil conditions, differences in precision of laboratory equipment with the tools used in the field, different forms of penetration characters in CBR testing.